Enhancing the thermal stability of n-type Mg3+xSb1.5Bi0.49Te0.01 by defect manipulation. (February 2023) - Xu, Congcong; Jian, Miaomiao; Liang, Zhongxin; Lei, Bing-Hua; Song, Shaowei; Zhang, Fanghao; Singh, David J.; Feng, Zhenzhen; Ren, Zhifeng
Abstract: N-type Mg3+x (Sb, Bi)2 -based thermoelectrics have quickly attracted considerable interest because of their excellent thermoelectric performance over a wide temperature range. Most studies on these compounds have thus far focused on improving their thermoelectric performance, with little consideration given to the equally essential issue of thermal stability. Mg3+x (Sb, Bi)2 is highly disordered due to having many kinds of defects, resulting in features like low thermal conductivity. However, the lattice distortion introduced by defects and the evolution of non-equilibrium defects both may impair the thermal stability of these thermoelectric materials. Additionally, incorporating Mg as the most prominent element in Mg3+x (Sb, Bi)2 has a significant impact on the compound's initial defect concentration and its stability performance at high temperatures due to Mg loss resulting from the element's high vapor pressure. Here we used in situ stability testing to reveal the evolution of intrinsic defects in n-type Mg3+x Sb1.5 Bi0.49 Te0.01 . A low-temperature annealing treatment was employed to improve stability by regulating non-equilibrium defects. Results from both experiments and theoretical calculations show that filling vacancy defects with transition metals rather than with additional excess Mg is effective in improving thermal stability due to the resulting enhanced chemical bonding and increased defect formation energy. This study has important implications for understanding and overcoming instability in other similar thermoelectric materials. Graphical Abstract: ga1 Highlights: Thermal stability is closely related to inherent defects in n-type Mg3+x Sb1.5 Bi0.49 Te0.01 . Non-equilibrium defects evolve with temperature and service time. Low-temperature annealing minimizes fluctuations in thermoelectric properties by stabilizing non-equilibrium defects. Replacing Mg with transition metals can enhance chemical bonding and increase defect formation energy.